Sustained censorship in SY (2026-03) (Syria) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Syria. Data sourced from OONI.
Censorship Incident ID: SY-2026-0103. Severity: critical. Confidence: 80%